Estudio comparativo de costos y rentabilidad de dos empresas familiares dedicadas a la producción de viveros de cítricos injertos en la zona norte del cantón Mocache, provincia de Los Ríos - Franco Vilela, Karen Karla (2017)
The study of this research project was carried out during the months of June to October 2017, with the objective of determining the production costs, profitability and the socio-economic profile of two family businesses dedicated to the production of citrus nurseries grafts in the north zone of the Mocache Canton, Province of Los Ríos, using the types of descriptive, explanatory, and field research, the analytical - synthetic, inductive - deductive, observation and scientific methods were also used for the development of research with the contribution of the primary and secondary sources that managed to provide the relevant data for the fulfillment of the research objectives. In the development of the work involved the producers of both companies who provided the necessary information to obtain the required data that were subsequently tabulated in the Microsoft Excel statistical program to obtain the results, in which it was determined that the family business "4 Brothers "in the elaboration of the six thousand citrus plants graft shows a production cost of $ 5,090.20, which generates an operating profit of $ 2,409.80, with a return on sales of 40%, while the company" Narcisa de Jesús" reflects a total cost of $ 4,735.68, which provides a profit before benefits and taxes of $ 2,764.32, with its profitability over sales of 46%, which means that this unit producing grafts earns $ 354.52 more than the previous one, therefore, it is in better economic conditions: although the propagation techniques and materials of the plants were similar between both companies. In the socioeconomic aspect this business is profitable for the two producers, which is why they want to continue with this activity, because it generates an extra in their economy which has allowed them to improve the quality of life of their families, they only need as a requisite to be registered in AGROCALIDAD to give stability to their sales and guarantee a high genetic potential. Key words: Cost of production, Profitability, Citrus grafts.